Understanding empowerment among retailers in the informal milk sector in peri-urban Nairobi: Informing an adaptation of the project-level Women's Empowerment in Agriculture Index - Myers, Emily (International Food Policy Research Institute, 2019)
Presented by Emily Myers (International Food Policy Research Institute), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.